Reliability of a new symptom score in a titrated quantitative conjunctival provocation test supported by an objective photodocumentation - Pfaar, Oliver; Claßen, Dan Philipp (International archives of allergy and immunology, 2018)
Background: Allergen provocation tests are useful methods for proving the clinical relevance of an allergen-specific sensitization. Among these methods, the conjunctival provocation test (CPT) represents an easy-to-use tool. However, its readout parameters have not yet been internationally standardized or validated. Photodocumentation has been shown as a good option for objectifying a CPT reaction, supporting the local investigator assessment. Based on test-retest reliability of the score and an objective digital photoanalysis of the conjunctival redness, this study aimed to prove the reproducibility of a new CPT scoring system for use in clinical trials (ClinicalTrials.gov identifier: NCT02690740). Methods: A titrated quantitative CPT was conducted outside of the pollen season in a final cohort of 23 adult patients with birch or grass pollen-induced allergic rhinoconjunctivitis. Conjunctival symptoms were analyzed using a standardized symptom score. Conjunctival redness was also evaluated by an external observer and correlated with a digital photoanalysis using MATLAB software. Results: A test-retest correlation of 0.6 (p < 0.01) was found for the symptom score results. Likewise, a correlation of 0.65 (p < 0.01) was observed in the digital photoanalysis. The total symptom score showed a decrease in the mean value of 0.48 score points in the retest. Conclusions: This study reveals both a valuable test-retest correlation of the proposed score as well as a good correlation of eye redness with the (objective) photodocumentation. Based on our results, we can recommend the use of this scoring system as a valuable clinical protocol for future clinical trials.